Magnetic trapping of SH radicals. Issue 12 (13th March 2017) - Eardley, J. S.; Warner, N.; Deng, L. Z.; Carty, D.; Wrede, E.
Abstract : Magnetic trapping of SH radicals, produced via the photostop technique, has been demonstrated. Abstract : Magnetic trapping of SH radicals, produced via the photostop technique, has been demonstrated. H2 S in a skimmed, supersonic molecular beam was photodissociated at 212.8 nm to produce SH inside a 330 mK deep static magnetic trap. The molecular-beam speed was controlled by the mixing ratio of H2 S in Kr to match the recoil velocity of the SH photofragments such that some SH radicals were produced with near-zero laboratory-frame velocity. The density of SH radicals in the 2 Π3/2, v = 0, J = 3/2 state was followed by (2 + 1) REMPI over seven orders of magnitude of signal intensity. 5 ms after photodissociation, SH radicals moving faster than the capture velocity of 13 m s −1 had left the trap. The 1/ e trap lifetime of the remaining SH radicals was 40 ± 10 ms at an estimated density of 5 × 10 4 molecules per cm 3 . Photostop offers a simple and direct way to accumulate absolute ground state molecules in a variety of traps.